2017
DOI: 10.21548/8-1-2324
|View full text |Cite
|
Sign up to set email alerts
|

Colour Changes in Blanc de Noir Wines during Ageing at Different Temperatures and its Colour Preference Limits

Abstract: Visual as well as spectrophotometrically measured colour changes were studied in six blanc de noir wines during ageing at 0, 10, 20°C and 30°C. Visual colour descriptions were compared with spectrophotometric measurements of absorbance at 420 nm and 520 nm, in order to obtain colour preference limits for this type of wine. A limit where the spectrophotometrically measured absorbance values at 420 nm and 520 nm do not exceed 0,200 and 0,160 respectively, was found best suited for this purpose. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Color is considered a significant quality indicator for both raw and processed agricultural products since it is the first item perceived by consumers. It has a great potential to attract the attention and perceptions of buyers (Ellis and Kok, 2017;Goñi and Salvadori, 2017). For instance, for walnuts, light colors are usually preferred by consumers (Fuentealba et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Color is considered a significant quality indicator for both raw and processed agricultural products since it is the first item perceived by consumers. It has a great potential to attract the attention and perceptions of buyers (Ellis and Kok, 2017;Goñi and Salvadori, 2017). For instance, for walnuts, light colors are usually preferred by consumers (Fuentealba et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The ones with symmetric or round shapes usually have higher market value than the others (Jun et al, 2017).Color is considered a significant quality indicator for both raw and processed agricultural products since it is the first item perceived by consumers. It has a great potential to attract the attention and perceptions of buyers (Ellis and Kok, 2017;Goñi and Salvadori, 2017). For instance, for walnuts, light colors are usually preferred by consumers (Fuentealba et al, 2017).The color of agricultural products is usually assessed through L*, a*, and b* values or CIELab color space (Goñi and Salvadori, 2017).…”
mentioning
confidence: 99%
“…For red wines, it has become a relatively basic consensus that the yellowing and browning caused by aging make the color gradually lose its attractive characteristics such as its purplish red and vividness and can even make it difficult to maintain an acceptable color [31,32]. It is conceivable and understandable that, according to the instrumental measurement and visual perception, aged red wines show relatively yellower, more gloomy, paler, and brighter macro-level colors than young wines.…”
Section: Macro-classification Methodsmentioning
confidence: 99%
“…Furthermore, previous studies have demonstrated that Glories’ method and the CIE L * a * b * color space cannot be used interchangeably for light red wines and white wines . The Glories method was originally developed for dark red wines but is now also used for rosé, white, and Blanc de Noir wines. Therefore, it is unclear whether the Glories color parameters reflect human perception of color outside of dark red wines. On the other hand, CIE color spaces should represent any aspect of perceived color, but it is uncertain whether it is able to do so in wine, given the experimental conditions, in which the CIE color spaces designed are completely different from those used during the sensory evaluation of wine color.…”
Section: Introductionmentioning
confidence: 99%